Research on Flow Characteristics of Electronically Controlled Injection Device Developed for High-Power Natural Gas Engines - Binbin Sun; Wenqing Ge; Yongjun Wang; Cao Tan; Bo Li (Journal of Engineering and Technological Sciences, 2019)
Accurate fuel supply is a key factor that influences the performance of high-power natural gas engines. The premixed and single-point natural gas supply system is the most commonly used method to ensure a large fuel supply but one of its shortcomings is the inaccuracy of the fuel supply. A new type of natural gas injection device with fungiform configuration and electronically controlled actuator was developed to achieve high efficiency and stable operation in high-power natural gas engines. Firstly, a computational fluid dynamics (CFD) model of the injection device was created. Based on this model, the key structure parameters that have a significant influence on the outlet flow were confirmed. A particle swarm optimization (PSO) model was developed to identify the optimal outflow structure. Then, a flow function for precise flow supply control was constructed based on a response surface model, according to the flow rates of the device under different control parameters. Finally, a flow-characteristic test bench and a high-power engine prototype were developed to verify the simulation and optimization results. The results indicate that the optimized outflow structure shows low pressure loss and a large flow rate, improving injection efficiency by 10.37% and mass flow by 11.78% under 0.4 Mpa pressure difference. More importantly, the cycle fuel supply could be controlled accurately for each cylinder owing to the developed flow function. Consequently, compared with the original engine using a single-point natural gas supply system, the cylinder performance imbalance was improved by 37.47%.